Measurement of the Consultation Duration in Otorhinolaryngology Outpatient Clinics: Comparison between a University Hospital and a City Hospital - Yamamura, Yukie; Kusama, Kaoru; Tomita, Erika; Nonaka, Manabu (International Journal of Practical Otolaryngology, 2022)
Materials and Methods The length of consultation per patient was measured by direct observation at the ear–nose–throat outpatient clinics of one university hospital and one city hospital. The consultation time was measured as follows. Direct consultation time: time spent on history-taking and physical examination of the patients. Indirect consultation time: time spent in charting, preparing treatment/prescription orders, medical, and writing referral letters.Results The total consultation time length was significantly longer at the university hospital than that at the city hospital, both for the first consultation and the follow-up consultation. For first visits, the ratio of the indirect consultation time to the total consultation time was 49.2% at the university hospital and 24.2% at the city hospital. As for follow-up visits, the indirect/total consultation time ratio was 37.8% at the university hospital 24.2% at the city hospital.Conclusion Assistance of a medical secretary would be desirable, especially for first consultations at the university hospital, in view of the long indirect consultation times.
Keywords: consultation duration; time; otorhinolaryngology; outpatient